PERAN SEKOLAH DALAM MEMBANGUN SIKAP TOLERANSI BERAGAMA - Karolina, Anita Ida; Rustiyarso, Rustiyarso; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research is based on the desire of researchers to know the role of the School in Building Religious Tolerance to the Students in SMA Negeri 3 Pontianak. The sub-problems in this study are as follows: 1. How is the concept of religious tolerance applied by the leadership in SMA Negeri 3 Pontianak? 2.How do the students respond to the concept of religious tolerance applied by the leadership in SMA Negeri 3 Pontianak? 3. How does the school leadership play a role in building religious tolerance in SMA Negeri 3 Pontianak? The purpose of this study was to determine the role of school in building religious tolerant attitudes towards students in Pontianak 3 senior high school. This research uses descriptive method with qualitative approach. The cooperation between school principles and teachers in the teaching about how important the attitudes of tolerance among people of Catholic,Protestant, Islam and Hindu also Budha. The teaching material given by the teacher is to grow love among the religious, love the differences around the school. However, school leaders and teachers are also provides guidance to students in keeping the relation then there is no division between students in different religions. The harmony happens will carry peaceful around the school environment so that the process of teaching and learning will success. Keywords: Attitudes, Religious, School Roles, Tolerance,